Further Validation of Triarchic Psychopathy Scales From the Multidimensional Personality Questionnaire: Setting the Stage for Large-Sample Etiological Studies. (July 2017) - Brislin, Sarah J.; Venables, Noah C.; Drislane, Laura E.; Blonigen, Daniel M.; Iacono, William G.; Tellegen, Auke; Edens, John F.; Patrick, Christopher J.
Psychopathy as conceptualized by the triarchic model encompasses three distinct dispositional constructs: boldness, meanness, and disinhibition. The current study sought to further validate triarchic (Tri) construct scales composed of items from the Multidimensional Personality Questionnaire (MPQ) as a foundation for advancing research on the etiology of psychopathy using existing large-scale longitudinal studies. MPQ-Tri scales were examined in three samples: mixed-gender undergraduate students ( N = 346), male offenders from a residential substance abuse treatment facility ( N = 190), and incarcerated female offenders ( N = 216). Across these three samples, the MPQ-Tri scales demonstrated high internal consistency and clear convergent and discriminant associations with criterion measures of psychopathy and other psychopathology outcomes. Gender comparisons revealed relatively few differences in relationships with criterion measures. Findings are discussed in terms of their implications for further investigation of the causal bases of psychopathy and other forms of psychopathology utilizing data from large etiologically informative studies.